2014
DOI: 10.1111/echo.12731
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Echocardiography Guided Closure of Complex Multiple Atrial Septal Defects

Abstract: Transcatheter closure of complex multiple atrial septal defects (ASDs) remains a challenge. We describe our clinical experience with staged device deployment in a patient with multiple ASDs using four Amplatzer septal occluder devices. Three-dimensional transesophageal echocardiography imaging contributed not only to the therapeutic guidance of successful device deployment but also to the decision making for the staged device delivery approach in a case of morphologically complex multiple ASDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Traditionally, TEE‐guided transcatheter ASD closures have been performed under general anesthesia with endotracheal intubation . Even though the efficacy of TEE‐guided transcatheter ASD closures has been well accepted with technologic advances, the cost and risk of general anesthesia are difficult to ignore …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, TEE‐guided transcatheter ASD closures have been performed under general anesthesia with endotracheal intubation . Even though the efficacy of TEE‐guided transcatheter ASD closures has been well accepted with technologic advances, the cost and risk of general anesthesia are difficult to ignore …”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Traditionally, TEE-guided transcatheter ASD closures have been performed under general anesthesia with endotracheal intubation. [8][9][10][11] Even though the efficacy of TEE-guided transcatheter ASD closures has been well accepted with technologic advances, [12][13][14][15][16][17][18] the cost and risk of general anesthesia are difficult to ignore. 19 Indeed, previous research has shown the application of TTE guidance for transcatheter closure of ASDs.…”
mentioning
confidence: 99%
“…Multiple ASDs remains a challenge for percutaneous closure because of residual shunt. 22 Zhu et al 23 In this study, all patients underwent intraoperative device closure got satisfactory results and avoided cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 61%
“…tic valve and deficient posterior or inferior rim may cause displacement of occluder. Stitching enhancement for cases with deficient posterior or inferior rim strengthens the stability of occluder to avoid from displacement.Multiple ASDs remains a challenge for percutaneous closure because of residual shunt 22. In this study, small-edge occluder (right disc>waist 3 mm different from normal occluder right disc > waist 5 mm) was employed and area rule was adopted for cases with deficient aortic or superior rim because of no "unbutton effect" in intraoperative device closure.…”
mentioning
confidence: 99%
“…2DTTE and TEE imaging techniques may not accurately depict the multiple defects of an ASD, whereas 3DTEE delineates the location, shapes, and sizes of the defects more precisely and shows the real anatomy of IAS. Furthermore, it is helpful in evaluating correct device position and orientation during transcatheter closure procedure . However, dropout artifacts make 3DTEE difficult to discriminate multiple defects of interatrial septum.…”
Section: Case Reportmentioning
confidence: 99%